Design of a Web-based Correspondence System Using the Codeigniter 3 Framework (Case study: Battuta University) - Intan Pratiwi, Dea Balqis; Harahap, Baginda; Ruziq, Fahmi (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
In the digital age, technology plays an important role in educational institutions such as Battuta University, helping in streamlining administrative processes and data management. The current reliance on Microsoft Excel for document management at the university proved to be inefficient, leading to issues such as misplaced documents, tracking difficulties, and difficulties in archivist management. To address these challenges, the development of a web-based document management system using the Codeigniter Framework is proposed. By utilizing this system, users can easily access and manage documents from various devices. So that the implementation of such a system is expected to improve the process of handling, tracking, and archiving documents, thus benefiting the university, especially in the field of correspondence.